2019
DOI: 10.1002/ps.5542
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and larvicidal activity against Aedes mosquitoes of essential oils from Arisaema fargesii

Abstract: BACKGROUND: Dengue fever is caused by the spread of dengue virus by Aedes mosquito vectors. Currently, the most effective way to control dengue is by preventing mosquitoes from spreading the disease. Arisaema fargesii is a Chinese herbal medicine commonly used to repel mosquitoes. In our laboratory, anti-mosquito chemical components were extracted from A. fargesii, and the effects of these substances on mosquito larvae were examined. RESULTS: In total, 48 compounds corresponding to 98.79% of the total oil were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…cassia essential oil and ( E )-cinnamaldehyde. Esterase and monooxygenase are involved in the metabolic detoxification of pesticides [ 33 ]. In ticks, they play an important role in the development of resistance to synthetic acaricides [ 18 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cassia essential oil and ( E )-cinnamaldehyde. Esterase and monooxygenase are involved in the metabolic detoxification of pesticides [ 33 ]. In ticks, they play an important role in the development of resistance to synthetic acaricides [ 18 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…cassia essential oil and ( E )-cinnamaldehyde. However, additional studies are needed to test different times of exposure, since esterase and monooxygenase activities may decrease with time [ 33 ], and to explore the contribution of other metabolic enzymes such as acetylcholinesterase and glutathione S-transferases to defense mechanisms. It is important to note that the total protein content of H .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the larvicidal activity of β-caryophyllene, α-humulene and germacrene D corroborates other larvicidal studies (Ravi et al 2006;Govindarajan and Benelli 2016a, b). Although caryophyllene oxide, α-terpineol, β-selinene and E-nerolidol were not investigated in our study, they are important larvicidal agents (Cheng et al 2004;Pavela 2015;Huang et al 2019), and could contribute through a synergic effect to the improvement of the larvicidal activity.…”
Section: Larvicidal Assaymentioning
confidence: 99%
“…aegypti and Ae. albopictus larvae [65]. Studies of different species have shown that thymol promoted toxicity in Plutella xylostella larvae, causing an increase in esterases levels, whereas in Ephestia kuehniella Zeller, inhibition of these enzymes was observed [66,67].…”
Section: Activity Of the Essential Oils Of L Grata On Enzymes Of The Larvae Of Ae Aegypti And Ae Albopictusmentioning
confidence: 99%